A study of the effect of culture on the learning of science in non-Western countries - Baker, David A. (Curtin University, 1998)
The research for this thesis was born of a desire to understand how a student's cultural background might influence the outcomes of science education. Of particular interest to me was the apparent paucity of academic achievement by many indigenous students as they study science through Western style schools and curricula, resulting in what I have termed 'educational alienation', which is evidenced by poor grades and slow rates of progression through the curriculum, and by some students displaying a high degree of antagonism toward the education system. 1 have sought to understand the causes of educational alienation by means of an interpretive inquiry based on a Grounded Theory methodology, using an Integrative Research Review as the primary means of data collection, supplemented by personal experience, data analysis and interview methods.The outcomes of the Grounded Research have caused me to re-think my understanding of culture and my tacit acceptance of conceptual change theory. Three distinct themes emerged as being significant to learning: Language Use, Traditional Beliefs and Life-world Knowledge. I have presented evidence suggesting that Language Use, Traditional Beliefs and Life-world Knowledge are largely subsumed within one's worldview, and that the term 'culture' lacks the specificity needed to explore the notion of educational alienation. I suggest that worldview is not only cultural, but is a dynamic belief system of the individual that is shaped by cultural forces and personal reflection, resulting in a reorganisation of knowledge throughout one's life. I propose that a constructivist view of learning and knowing presents us with a plausible explanation of worldview development and educational alienation, and I conclude with suggestions for further research and pedagogy that might develop the discourse and consequently improve the outcomes of science education for indigenous, non-Western students.